2006
DOI: 10.1117/1.2363366
|View full text |Cite
|
Sign up to set email alerts
|

Use of glycerol as an optical clearing agent for enhancing photonic transference and detection of Salmonella typhimurium through porcine skin

Abstract: The objective of this study was to evaluate glycerol (GLY) and GLY + dimethyl sulfoxide (DMSO) to increase photonic detection of transformed Salmonella typhimurium (S. typh-lux) through porcine skin. Skin was placed on 96-well plates containing S. typh-lux, imaged (5 min) using a CCD camera, and then completely immersed in PBS, GLY, DMSO, GLY+DMSO in a dose- and time-dependent manner and re-imaged (5 min). The percent of photonic emissions detected (treated or untreated skin relative to no skin controls) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The use of bioluminescent bacteria, such as E. coli-pAKl-lux or E. coZi!-Xenl4, coupled with bioluminescence imaging technologies, may represent an efficient model for achieving a greater understanding of the pathogenesis of uterine and placental infections in domestic species. Some studies have established positive relationships between bioluminescent signals and bacterial populations for gram-negative bacteria (r = 0.99; Kadurugamuwa et al, 2005), whereas other investigators have described and validated bioluminescent bacterial models, both in vitro (Moulton et al, 2006(Moulton et al, , 2009c and ex vivo (Moulton et al, 2009a,d;Curbelo et al, 2010). More recently, studies have reported the use of bioluminescent reporters and biophotonic imaging technology to study mechanisms of pathogenesis of such pathogens as Staphylococcus aureus (Kuklin et al, 2003), Aspergillus fmnigatus (Brock et al, 2008), Listeria monocytogenes (Konjufca and Miller, 2009), E. coli (Foucault et al, 2010), and Mycobacterium tuberculosis (Andreu et al, 2010); however, these studies have focused on the use of the mouse model.…”
Section: Genetically Modified Bacteria With the Lux Genementioning
confidence: 96%
“…The use of bioluminescent bacteria, such as E. coli-pAKl-lux or E. coZi!-Xenl4, coupled with bioluminescence imaging technologies, may represent an efficient model for achieving a greater understanding of the pathogenesis of uterine and placental infections in domestic species. Some studies have established positive relationships between bioluminescent signals and bacterial populations for gram-negative bacteria (r = 0.99; Kadurugamuwa et al, 2005), whereas other investigators have described and validated bioluminescent bacterial models, both in vitro (Moulton et al, 2006(Moulton et al, , 2009c and ex vivo (Moulton et al, 2009a,d;Curbelo et al, 2010). More recently, studies have reported the use of bioluminescent reporters and biophotonic imaging technology to study mechanisms of pathogenesis of such pathogens as Staphylococcus aureus (Kuklin et al, 2003), Aspergillus fmnigatus (Brock et al, 2008), Listeria monocytogenes (Konjufca and Miller, 2009), E. coli (Foucault et al, 2010), and Mycobacterium tuberculosis (Andreu et al, 2010); however, these studies have focused on the use of the mouse model.…”
Section: Genetically Modified Bacteria With the Lux Genementioning
confidence: 96%
“…[1][2][3]5 Higher-concentrated glycerol ͑75%, 100%͒ and glucose ͑40%͒ have great optical clearance of tissue, but the less-concentrated glucose solutions ͑35% to 20%, 10 L͒ have slight clearance. 24,25 Moreover, the agents have also been applied to study short-term effects on blood vessels.…”
Section: Optical Clearing Agentsmentioning
confidence: 99%
“…The tissue optical clearing technique based on immersion of tissues into optical clearing agents, proposed by Tuchin, [1][2][3][4] can improve the depth to which light penetrates, and currently attracts great attention. This technique, combined with other optical imaging techniques, such as optical coherence tomography ͑OCT͒, 2,3,14 fluorescence imaging, 5,6 microscopy imaging, 7,8 and laser radiation, 9,10 etc. will enhance the capabilities of noninvasive optical diagnosis and therapeutic treatments.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other people measured optical properties to find out the optical clearing effect [20][21]. Jinhee Yoon Author is with the Department of biomedical Engineering, Yonsei University, South Korea (e-mail: no-fate@yonsei.ac.kr).…”
Section: Introductionmentioning
confidence: 98%